Genetic Relationship among Chicken Populations of India Based on SNP Markers of Myostatin Gene (GDF 8) - Kumar, S. T. Bharani; Dilbaghi, Neeraj; Ahlawat, S.P.S.; Mishra, Bina; Tantia, M.S.; Vijh, R.K. (International Journal of Poultry Science, 2007)
The data on ten SNP markers of Myostatin gene (GDF-8) was generated on nine breeds/populations of indigenous poultry and Red Jungle Fowl (RJF). The SNPs were five in promoter region, one each in intron 1 and 2 and three in exon 1. The data was analyzed to find out the genetic relationship among the indigenous chicken populations. PCR-RFLP was carried out to genotype the populations at seven SNPs while three were genotyped by SNaPshot method using automated DNA sequencer as no restriction sites were found at the SNP sites. ANOVA revealed 18% of the variation among the populations. The correspondence analysis separated out Punjab Brown, Red jungle fowl and Nicobari populations from the rest of the indigenous chicken populations. It is postulated that the populations of Punjab Brown and Nicobari showed the recent common ancestry with Red jungle fowl.